Comparison of survival, palliation, and quality of life with three chemotherapy regimens in metastatic colorectal cancer: a multicentre randomised trial. - Maughan, T; James, R; Kerr, D; Ledermann, J; McArdle, C; Seymour, M; Cohen, D; Hopwood, P; Johnston, C; Stephens, R (2002)
BACKGROUND: This randomised trial compared three chemotherapy regimens in the first-line treatment of advanced colorectal cancer, in terms of their effect on overall and progression-free survival; other endpoints included toxicity, symptom palliation, and quality of life. METHODS: 905 patients were randomly assigned the de Gramont regimen (n=303; folinic acid 200 mg/m(2), fluorouracil bolus 400 mg/m(2), and infusion 600 mg/m(2) on days 1 and 2, repeated every 14 days), the Lokich regimen (n=301; protracted venous infusion of fluorouracil 300 mg/m(2) daily), or raltitrexed (n=301; 3 mg/m(2) intravenously every 21 days). Analyses were by intention to treat. FINDINGS: Median follow-up of survivors was 67 weeks. For the de Gramont, Lokich, and raltitrexed groups, respectively, median survival was 294, 302, and 266 days. The hazard ratios for overall survival were 0.88 (95% CI 0.70-1.12, p=0.17) for de Gramont versus Lokich, and 0.99 (0.79-1.25, p=0.94) for de Gramont versus raltitrexed. An increase in treatment-related deaths was seen on raltitrexed (de Gramont one, Lokich two, raltitrexed 18) due to combined gastrointestinal and haematological toxicity. Patients' assessment of quality of life showed that raltitrexed was inferior to the fluorouracil-based regimens, especially in terms of palliation and functioning. INTERPRETATION: The deGramont and Lokich regimens were similar in terms of survival, quality of life, and response rates. The Lokich regimen was associated with more central line complications and hand-foot syndrome. Raltitrexed showed similar response rates and overall survival to the de Gramont regimen and was easier to administer, but resulted in greater toxicity and inferior quality of life.